Separacenes A–D, Novel Polyene Polyols from the Marine Actinomycete, Streptomyces sp - Bae, Munhyung (MDPI, 2013)
Separacenes A–D (1–4), novel polyene polyols, were isolated from Streptomyces sp. collected from the southern area of Jeju Island, Korea. The chemical structures of 1–4 were established by NMR, mass, UV, and IR spectroscopy as well as the modified Mosher’s method. Separacenes A–B (1–2), which share an identical planar structure but possess different relative configurations, bear tetraene units flanked by two diol moieties, whereas the stereoisomeric separacenes C–D (3–4) possess a triene moiety between two diol substructures. Separacenes A–D each contain a terminal olefinic methylene. Separacene A displayed inhibitory activity against Candida albicans isocitrate lyase and weak cytotoxicity against both the colon carcinoma cell line HCT-116 and the lung cancer cell line A549.